Use of CT Imaging to Quantify Progression and Response to Treatment in Lymphangioleiomyomatosis - Gopalakrishnan, Vissaagan (Chest, 2019)
BACKGROUND: In lymphangioleiomyomatosis (LAM), infiltration of the lungs with smooth muscle-like LAM cells results in cystic destruction and decline in lung function, effects stabilized by sirolimus therapy. LAM lung disease is followed, in part, by high-resolution CT scans. To obtain further information from these scans, we quantified changes in lung parenchyma by analyzing image “texture.” METHODS: Twenty-six texture properties were quantified by analyzing the distribution and intensity of pixels with a computer-aided system. Both cross-sectional and longitudinal studies were performed to examine the relationships between texture properties, cyst score (percentage of lung occupied by cysts), FEV(1), and diffusion capacity for carbon monoxide (Dlco), and to determine the effect of sirolimus treatment. RESULTS: In the cross-sectional study, 18 texture properties showed significant positive correlations with cyst score. Cyst score and 13 of the 18 texture properties showed significant differences in rates of change after sirolimus treatment; 11 also significantly predicted FEV(1) and Dlco. CONCLUSIONS: Increased cyst score was associated with increased texture degradation near cysts. Sirolimus treatment improved lung texture surrounding cysts and stabilized cyst score. Eleven texture properties were associated with FEV(1), Dlco, cyst score, and response to sirolimus. Texture analysis may be valuable in evaluating LAM severity and treatment response.